Understanding time-to-recovery among Guatemalan Children before and during COVID-19 - Morgan E. Braxton; Kim L. Larson; Carlos R. Melendez (Elsevier, 2023)
Purpose: To understand malnutrition recovery at a Guatemalan Nutrition Rehabilitation Center (NRC) before and during the COVID-19 pandemic. Design and methods: A retrospective chart review was conducted on-site in November 2022. The NRC is located on the outskirts of Antigua, Guatemala. They manage the care of 15-20 children at a time, providing food, medicine, and health assessments. A total of 156 records were included (126 prior to the onset of COVID; 30 after the onset of COVID). Descriptive variables collected were age, gender, severity of malnutrition, height, weight, amoxicillin, multivitamins, nebulizer/bronchodilator, and zinc. Principal results: There was no significant difference in time-to-recovery between COVID cohorts. Mean time-to-recovery was 5.65 weeks, or 39.57 days (SD = 25.62, 95% CI [35.5, 43.7]) among all recovered cases (n = 149). The cohort admitted after the onset of COVID-19 (March 1, 2020) had a significantly higher weight gain and discharge weight. In the total sample, amoxicillin was the only significant predictor variable for recovery time; with children receiving it being more likely to recover in >6 weeks. The few differences between cohorts was possibly attributed to the sample after the onset of COVID-19. These records had minimal sociocultural data. Major conclusions: Conducting a family needs assessment on admission could identify sociocultural factors that may facilitate nutritional recovery, such as housing conditions and potable water access. Further research is needed to more fully understand the complexities that the COVID-19 pandemic has had on childhood malnutrition recovery.